Multivitamins and minerals modulate whole-body energy metabolism and cerebral blood-flow during cognitive task performance: a double-blind, randomised, placebo-controlled trial. Issue 1 (December 2016) - Kennedy, David; Stevenson, Emma; Jackson, Philippa; Dunn, Sarah; Wishart, Karl; Bieri, Gregor; Barella, Luca; Carne, Alexandra; Dodd, Fiona; Robertson, Bernadette; Forster, Joanne; Haskell-Ramsay, Crystal
Abstract Background The brain is by far the most metabolically active organ in the body, with overall energy expenditure and local blood-supply closely related to neural activity. Both energy metabolism and cerebral vaso-dilation are dependent on adequate micronutrient status. This study investigated whether supplementation with ascending doses of multi-vitamin/minerals could modulate the metabolic and cerebral blood-flow consequences of performing cognitive tasks that varied in difficulty. Methods In this randomised, double-blind, placebo-controlled, parallel-groups study 97 healthy females (25–49 y), who were not selected on the basis of any nutritional parameters, received either placebo or one of two doses of multivitamins/minerals. Cerebral blood-flow (CBF) parameters in the frontal cortex, and total energy expenditure (TotalEnergy), carbohydrate and fat oxidation (CarbOxi/FatOxi), were measured during 5 tasks of graded cognitive difficulty and a control task (5 min per task) using Near-infrared spectroscopy (NIRS) and Indirect calorimetry of exhaled pulmonary gas (ICa) respectively. Assessments took place 60 min after the first dose and following eight weeks supplementation. Results During task performance supplementation with the first dose of micronutrients led to a dose-dependent increase in TotalEnergy and FatOxi throughout the post-dose assessment period following the higher dose, and increases in the total concentration of haemoglobin, a proxy measure for CBF, during task performance following the lower dose of vitamins/minerals (also containing coenzyme-Q10). Chronic supplementation over 8 weeks led to a dose-dependent increase in TotalEnergy during the task period. There were no interpretable effects on mood or cognitive performance. Conclusions These results show that acute supplementation with micronutrients in healthy adults can modulate metabolic parameters and cerebral blood flow during cognitive task performance, and that the metabolic consequences are sustained during chronic supplementation. These findings suggest that both brain function and metabolism are amenable to micronutrient supplementation, even in adults who are assumed to have nutritional status typical of the population. Trial registration ClinicalTrials.gov -NCT02381964 .